The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/rfe.1078
|View full text |Cite
|
Sign up to set email alerts
|

Investing in the S&P 500 index: Can anything beat the buy‐and‐hold strategy?

Abstract: Determining whether investment strategies exist that provide higher (risk‐adjusted) returns than buying and holding the S&P 500 stock market index is not only highly relevant for finance theory, but also for the asset management industry. This study conducts a comprehensive test using realistic investment strategies based on monthly seasonalities, technical indicators, and fundamental factors (over 4,100 strategies in total). To assess statistical significance, we use Hansen's data‐snooping‐resistant SPA test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 109 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…In this respect, an uncomplicated moving‐average (MA) method (Büyükşahin & Ertekin, 2019; Liu, Sun, et al, 2020) is expected to remove the strong assumptions created by statistical models through the process of component decomposition and become an alternative approach for multiscale preprocessing. The MA filter operates as an optimal indicator, decomposing a variable to its components, for example, random noise and trend, and revealing overreaction and underreaction effects (Dichtl, 2020). However, the MA filter functionality in the decomposition task that is, the smoothing process on impulsive interference, is not ideal with large response delay drawback as many low‐pass filters (de Almeida et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, an uncomplicated moving‐average (MA) method (Büyükşahin & Ertekin, 2019; Liu, Sun, et al, 2020) is expected to remove the strong assumptions created by statistical models through the process of component decomposition and become an alternative approach for multiscale preprocessing. The MA filter operates as an optimal indicator, decomposing a variable to its components, for example, random noise and trend, and revealing overreaction and underreaction effects (Dichtl, 2020). However, the MA filter functionality in the decomposition task that is, the smoothing process on impulsive interference, is not ideal with large response delay drawback as many low‐pass filters (de Almeida et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The research concluded that the buy and hold strategy is also superior in seasonality aspects. The commonness of trading strategies using moving averages is understandable due to its ability to generate returns, which are adjusted to the risk and the ability to generate a positive alpha in comparison to other risk factors, especially when the market is highly volatile (Dichtl, 2020). Current literature indicates that there is a direct relation between the volume of stock traded and the prices of stocks in the Arab markets.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“… The performance of the S&P 500 is also a popular benchmark for technical trading strategies (see Dichtl, 2020). …”
mentioning
confidence: 99%